Insecticidal and Acetylcholinesterase Inhibition Activity of Veratrum nigrum Alkaloidal Extract against the German Cockroach (Blattella germanica) - Xianghai Cai; Qingfeng Li; Lei Xiao; Hailiang Lu; Jian Tang; Jianbo Huang; Jianzhong Yuan (Tehran University of Medical Sciences, 2018)
Background: Veratrum nigrum (Liliaceae) is perennial medicinal plant widely used to treat various conditions. To determine its insecticidal properties against the German cockroach (Blattella germanica), several laboratory tests were carried out. Methods: A 4kg dry sample of V. nigrum root was purchased from the medicinal material market in Yunnan Province in 2015, China. In contact toxicity tests, V. nigrum alkaloidal extract was topically applied to the abdomen of cockroaches using a micro-applicator. In vitro acetylcholinesterase (AChE) activity tests were performed using a modified Ellman method. Results: Veratrum nigrum alkaloidal extract was toxic to male adults and 4th nymphs cockroaches, with median lethal dose (LD50) values of 14.90µg/insect, 14.21µg/insect for adults and 41.45µg/insect, 39.01µg/insect for 4th nymphs after 24h and 48h exposure, respectively. There was a significant difference between adults and nymphs in terms of tolerance to V. nigrum alkaloidal extract. There was no significant difference in mortalities at 24h and 48h, the lethal effect of V. nigrum alkaloidal extract on German cockroach was quick. AChE activity tests showed that V. nigrum alkaloidal extract had an excellent inhibitory effect on AChE: inhibition in the 4th nymphs and male adults had 50% inhibiting concentration (IC50) values of 3.56mg/ml and 5.78mg/ml respectively. The inhibitory effect of AChE activity was positively correlated with inhibitory time (0-20min), at a concentration of 1mg/ml, inhibition of nymph and adult AChE activity had 50% inhibiting time (IT50) values of 8.34min and 16.75min, respectively. Conclusion: V. nigrum may be explored as a potential natural insecticide for control of the German cockroach.